Separation of Cerium, Neodymium, and Lanthanum from Rare Metal Concentrates by Calcining and Leaching Using Hydrochloric Acid - Alfawwazi, Abdul Fattah; Setyadji, Much.; Jumaeri, Jumaeri (Universitas Negeri Semarang, 2022)
The separation of Ce, La, and Nd elements from rare earth metal (REOH) concentrates from monazite sand processing needs to be done because the uses of La and Nd in the industry are very large. This research was conducted to determine the optimization of leaching in the separation of Ce, La, and Nd. The method used to separate the elements Ce, La, and Nd from the rare earth metal concentrate is through calcination at a temperature of 600°, 800°, 1000°C for 2 hours and without calcination, followed by a leaching process using 0.9 M HCl solvent at a temperature of 75°C. Variations made are the ratio of solid and liquid ratio and variations in time (5, 10, 15, 20, and 25 minutes), and the stirring speed is fixed at 150 rpm. From the results of FT-IR and XRD analysis, it is known that calcination can convert REOH concentrate into REO. Residual analysis of leaching results using XRF showed that the increase in calcination temperature with a solid and liquid ratio and leaching time could affect the leaching efficiency results. The highest leaching efficiency for the element La was obtained at a calcination temperature of 1000°C with a time of 10 minutes, which was 73.20%. Meanwhile, the optimum condition for the best leaching process for Nd is at a calcination temperature of 1000°C with a contact time of 5 minutes with a leaching efficiency of 49.68%.